Interactions of artificial lakes with groundwater applying an integrated MODFLOW solution - El-Zehairy, A.A.M.E. (2020)
Artificial lakes (reservoirs) are regulated water bodies with large stage fluctuations and different interactions with groundwater compared with natural lakes. A novel modelling study characterizing the dynamics of these interactions is presented for artificial Lake Turawa, Poland. The integrated surface-water/groundwater MODFLOW-NWT transient model, applying SFR7, UZF1 and LAK7 packages to account for variably-saturated flow and temporally variable lake area extent and volume, was calibrated throughout 5 years (1-year warm-up, 4-year simulation), applying daily lake stages, heads and discharges as control variables. The water budget results showed that, in contrast to natural lakes, the reservoir interactions with groundwater were primarily dependent on the balance between lake inflow and regulated outflow, while influences of precipitation and evapotranspiration played secondary roles. Also, the spatio-temporal lakebed-seepage pattern was different compared with natural lakes. The large and fast-changing stages had large influence on lakebed-seepage and water table depth and also influenced groundwater evapotranspiration and groundwater exfiltration, as their maxima coincided not with rainfall peaks but with highest stages. The mean lakebed-seepage ranged from ~0.6 mm day−1 during lowest stages (lake-water gain) to ~1.0 mm day−1 during highest stages (lake-water loss) with largest losses up to 4.6 mm day−1 in the peripheral zone. The lakebed-seepage of this study was generally low because of low lakebed leakance (0.0007–0.0015 day−1) and prevailing upward regional groundwater flow moderating it. This study discloses the complexity of artificial lake interactions with groundwater, while the proposed front-line modelling methodology can be applied to any reservoir, and also to natural lake interactions with groundwater.